Using science songs for engaging Generation Y students - Yee, Isabel Pin Tsin * (2014)
Songs have demonstrated to be effective teaching and learning tools in young children. However, their efficacy remains to be investigated upon its usage for Generation Y students. Research on the use of science songs in middle school classes suggests that revisiting lecture content in an alternative form such as using lyrics, tests students' understanding in a way that cannot be achieved by a lecture. In this research, songs based on the more difficult subtopics in Medical Biotechnology and Chemistry was composed, encompassing many formulas, equations and facts to be remembered. This technique of song composition can be used in any subject and any tune can be used. Songs can be utilized for any class size, from tutorials to lecture halls. Students found it very enjoyable and stress-reducing when learning complex scientific facts. It added variety to their learning experiences and engaged Generation Y students more effectively through a variety of modalities and modes simultaneously.